Semiautomatic and fully functional electrochemical microanalyzer BO-05 suitable for scientific, didactic, and analytical applications: The use in the potentiometric analysis of drugs - Opoka, Włodzimierz; Szlósarczyk, Marek; Chojnacki, Adam; Kryczyk-Poprawa, Agata; Talik, Przemysław; Gál, József; Muszyńska, Bożena; Baś, Bogusław (Analecta Technica Szegedinensia, 2021)
This article presents the potentiometric method of determination of chlorides using the original BO-05 electrochemical microanalyzer. The quantification of chlorides is one of the frequently performed methods, both in the indirect determination of active pharmaceutical ingredients (API) and impurities in pharmaceutical raw materials, pharmacopoeial substances or pharmaceutical formulations as well. Successfully validated method was used to the analysis of chlorides in the preparations containing verapamil hydrochloride in form of tablets Staveran® and Verapamil®. The mean content of the studied API calculated to one tablet was close to the declared and equal to 123.6±1.5 mg and 122.6±1.1 mg, respectively. The presence of excipients have no significant impact on the final results. Thus shown that the electrochemical microanalyzer BO-05 is suitable for scientific, didactic and analytical applications.